A Review of HRV and EEG Technology Applications in Industry 5.0: Emphasising Manufacturing Efficiency and Worker Well-Being - Chulakit, Saranjuu; Sadun, Amirul Syafiq; Jalaludin, Nur Anija; Hashim, Hairulazwan; Hassan, Hasliza; Mahmood, Salwa; Marsi, Noraini; Muhammad Ashraf Fauzi, (International Journal of Integrated Engineering, 2024)
This review paper examines the role of physiological monitoring techniques in the manufacturing industry, particularly through the use of Heart Rate Variability (HRV) and Electroencephalography (EEG), aligning with the human-centric approach of Industry 5.0. Delving into the current applications and potential of these biometric tools, the paper highlights their significance in enhancing worker well-being, safety, cognitive workload management, and the optimisation of human-machine interactions. A systematic literature search employing the PRISMA framework was conducted, revealing a marked preference for HRV over EEG in current research, although both have been shown to offer substantial benefits. The review underscores the precision of ECG-based HRV measurements as pivotal for assessing autonomic nervous system activity, with implications for employee health outcomes. The analysis of EEG studies reflects its utility in mapping psychological states and fostering advanced Brain-Computer Interface technologies, contributing to safer and more efficient manufacturing processes. As the review concludes, the integration of HRV and EEG monitoring is poised to become a standard practice within the industry, signalling a shift towards manufacturing operations that prioritize the health and satisfaction of the workforce while maintaining operational excellence. The findings advocate for the adoption of these monitoring techniques as part of a larger strategy to ensure a responsive, adaptive, and worker-centric manufacturing environment. This paper paves the way for future research to explore the full spectrum of possibilities that HRV and EEG monitoring hold for the evolution of the manufacturing sector.